Determination of rainfall pattern and flow rate at Tasik Chini - Noor ‘Aina Mardhiah, Hanapi (2017)
This research described analysis studies on the collected secondary data in order to identify the rainfall pattern in Tasik Chini. The collected data be used for research and planning the activities surrounding Tasik Chini area. The rainfall data are collected from Jabatan Pengairan dan Saliran (JPS) and a new hydrological station which is was set up at Kampung Melai. For JPS, the hydrological station had be chosen for this study are at Kampung Batu Gong, Paya Membang and Kampung Salong with station number 3330109, 3430097 and 3429096 respectively. While, the new hydrological station is Kampung Melai. This location was selected because of it is closed to the River Jemberau and Sungai Chini which closed to logging and mining activities. After that, all the rainfall data are used to analysis and calculate the total annual rainfall and total monthly rainfall for four Rainfall Hydrology Station at Tasik Chini with 10 years duration to get the highest value of rainfall. The closed Hydrology Station in Tasik Chini were chosen refer to the Hydrology Station stated in MSMA2. The function of the Hydrology Station is to calculate the Rainfall Intensity of the location with the highest total value of rainfall. For Station of Paya membang the highest average monthly rainfall is 811 mm (between 2008 until 2017). While, the highest average monthly rainfall for Kampung Batu Gong Station and Kampung Salong Station are 449 mm and 549 mm respectively. Compare to the Kampung Melai Station, the amount average monthly rainfall is 435.4 mm. A single formula was applied to all rainfall data of all average recurrence intervals (ARIs). ARIs used were ranging from 5 years ARI 10 years ARI, 20 years ARI, 50 years ARI and 100 years ARI. Hydrological analysis was used to gather data. The IDF Curves were developed for durations of 5 minutes, 15 minutes, 60 minutes, 180 minutes, 360 minute, 720 minutes, 1440 minutes, 2880 minutes and 4320 minutes. Later, the second objective of the study is achieved by determine and analysis the flow rate at Sungai Jemberau and Sungai Chini (Navigation Lock). From the analysis the highest flow rate is 4.382 m3/s which is at Sungai Chini (Navigation Lock). While, the lowest flow rate also at Sungai Chini (Navigation Lock) with 0.0 m3/s.